ANALISIS DEMPSTER SHAFER PADA SISTEM PAKAR PENDETEKSI PENYAKIT ISPA - Harliana; Wiwi Widayani (LPPM STMIK El Rahma Yogyakarta, 2019)
ISPA is a serious disease that can occur in the community, even ISPA can also be the main killer of a baby's death. Symptoms caused by ISPA are almost the same as the symptoms of other diseases, so sometimes doctors or assistant doctors have difficulty diagnosing this disease. This study discusses the detection of ISPA through the dampstershafer method and the researchers will test the accuracy of the results obtained. Based on the test results through the matrix confusion of 100 patients and 13 types of ISPA, it produces an accuracy value of 95% with a 5% error rate and this is in accordance with the diagonosa produced by the doctor.